A time to keep silence - Fermor, Patrick Leigh (New York Review Books classics., 2007)
Patrick Leigh Fermor set off as a teenager to make his way across Europe, as recorded in his classic memoirs, A Time of Gifts and Between the Woods and the Water. Later he fought with local partisans against the Nazi occupiers of Crete. A Time to Keep Silence stands out among Fermor's various tales of travel and adventure because it is more an inward than an outward voyage. Here Fermor chronicles his several sojourns in some of Europe's oldest and most celebrated monasteries. He stays at the Abbey of Wandrille, a great repository of art and learning; at Solesmes, famous for its revival of Gregorian chant; and at the deeply ascetic Trappist monastery of La Grande Trappe, where monks take a vow of silence. Finally, he visits the rock monasteries of Cappadocia, hewn from the stony spires of a moonlike landscape, where he seeks some trace of the life of the earliest Christian anchorites. This beautiful short book is a meditation on the meaning of silence and solitude for modern life. Fermor writes, In the seclusion of a cell--an existence whose quietness is only varied by the silent meals, the solemnity of ritual, and long solitary walks in the woods--the troubled waters of the mind grow still and clear, and much that is hidden away and all that clouds it floats to the surface and can be skimmed away; and after a time one reaches a state of peace that is unthought of in the ordinary world.